Use of Assisted Reproduction Techniques in Male Pathologies: Molecule Based Sperm Selection Methods - Marini, Patricia Estela (2017)
Fil: Fil: Teijeiro, Juan Manuel. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Laboratorio de Medicina Reproductiva; Argentina.